MUMMIFIED FOETUS AND PUP WITH EVISCERATED INTESTINE IN A PUG BITCH - KUMAR, SUDHIR; SHARMA, UTSAV; KUMAR, SHARAD; KUSHWAHA, R B; DWIVEDl, D K (The Indian Journal of Animal Reproduction, 2023)
The present study reports a case of mummified fetus and pup with protruded intestine in a bitch delivered after full term.